Novel In Situ Growth of ZIF-8 in Porous Epoxy Matrix for Mechanically Robust Composite Electrolyte of High-Performance, Long-Life Lithium Metal Batteries - Wenjie Zhang; Jianlin Long; Haijun Wang; Jinle Lan; Yunhua Yu; Xiaoping Yang (Molecules, 2022)
Polymer electrolytes (PEs) with high flexibility, low cost, and excellent interface compatibility have been considered as an ideal substitute for traditional liquid electrolytes for high safety lithium metal batteries (LMBs). Nevertheless, the mechanical strength of PEs is generally poor to prevent the growth of lithium dendrites during the charge/discharge process, which seriously restricts their wide practical applications. Herein, a mechanical robust ZIF-8/epoxy composite electrolyte with unique pore structure was prepared, which effectively inhibited the growth of lithium dendrites. Meanwhile, the in situ growth of ZIF-8 in porous epoxy matrix can promote the uniform flux and fast transport of lithium ions. Ultimately, the optimal electrolyte shows high ionic conductivity (2.2 × 10−3 S cm−1), wide electrochemical window (5 V), and a large Li+ transference number (0.70) at room temperature. The Li||NCM811 cell using the optimal electrolyte exhibits high capacity and excellent cycling performance (83.2% capacity retention with 172.1 mA h g−1 capacity retained after 200 cycles at 0.2 C). These results indicate that the ZIF-8/epoxy composite electrolyte is of great promise for the application in LMBs.